Pacman Game Benefit Analysis on Decision Making Speed - Wati Wulandari; Bernardinus Harnadi (SISFORMA, 2014)
Pacman game is able to train the child concentration and decision making speed. This Research use respondent children ages 6 up to11 years as a player who will take the data. Every respondent must play Pacman game and then they can answer 10 questions. Resulting data are analyzed with a statistical method; it is product moment" in correlation technique. The result turns out 8 of the 10 children get correlation values above 0.632. From the results of these research demonstrate that children who play the Pacman has the ability to quick in decision making and to have high concentrations. Because playing the game using the right brain or our imagination so that when applied in real life we are trained to improve concentration and have a strategy in solving the problem.Keyword: decision making, respondent children, statistical method, product moment